2013
DOI: 10.1371/journal.pgen.1003861
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bHLH Proteins form Heterodimers to Mediate CRY2-Dependent Regulation of Flowering-Time in Arabidopsis

Abstract: Arabidopsis thaliana cryptochrome 2 (CRY2) mediates light control of flowering time. CIB1 (CRY2-interacting bHLH 1) specifically interacts with CRY2 in response to blue light to activate the transcription of FT (Flowering Locus T). In vitro, CIB1 binds to the canonical E-box (CACGTG, also referred to as G-box) with much higher affinity than its interaction with non-canonical E-box (CANNTG) DNA sequences. However, in vivo, CIB1 binds to the chromatin region of the FT promoter, which only contains the non-canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
181
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 60 publications
4
181
0
2
Order By: Relevance
“…6). We recently showed that CIB1 acts redundantly with its related proteins, CIB2, CIB4, and CIB5, to promote floral initiation and that these CIB1-related proteins are similarly degraded in the absence of blue light and stabilized in blue light in a ZTL-dependent manner (28). The ZTL/LKP2-mediated blue-light regulation of multiple CRY2-interacting CIB proteins provides a molecular mechanism to coordinate the functions of these two different types of photoreceptors in the control of plant development.…”
Section: Discussionmentioning
confidence: 99%
“…6). We recently showed that CIB1 acts redundantly with its related proteins, CIB2, CIB4, and CIB5, to promote floral initiation and that these CIB1-related proteins are similarly degraded in the absence of blue light and stabilized in blue light in a ZTL-dependent manner (28). The ZTL/LKP2-mediated blue-light regulation of multiple CRY2-interacting CIB proteins provides a molecular mechanism to coordinate the functions of these two different types of photoreceptors in the control of plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors, CIBs (CIB1, CIB2, CIB4, and CIB5), redundantly activate FT expression (Liu et al, 2008a(Liu et al, , 2013c. CIBs form various combinations of heterodimers that possess higher affinities to E-box sequences (CANNTG).…”
Section: Transcriptional Regulation Of Ftmentioning
confidence: 99%
“…This difference in the response to light quality between the ft mutant and the wild type in A. thaliana seems to have commonalities with the difference between 'Bristol Fairy' and 'Million Star' in G. paniculata. We analyzed the G. paniculata homologs of FKF1 (Hori et al, 2011). An E-box and TCTAG motif, which may be important in blue light-dependent FT expression (Liu et al, 2013;Shaikhali et al, 2012), were found in this region from MS.…”
Section: Discussionmentioning
confidence: 85%
“…7). The deleted region contained an E-box (CANNTG) and a TCTAG se- quence, which are reportedly associated with the response to blue light through the CRY pathway (Liu et al, 2013;Shaikhali et al, 2012).…”
mentioning
confidence: 99%